Economics Dynamics Problems 62

Economics Dynamics Problems 62 - x ( t ) = x e kt In other...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
46 Economic Dynamics Figure 2.9. Hence integrating both sides with respect to t gives ± dx dt 1 x dt = ± kdt + c 0 ln x = kt + c 0 x ( t ) = ce kt which gives the solution
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: x ( t ) = x e kt In other words, we could solve x ( t ) explicitly in terms of t ....
View Full Document

Ask a homework question - tutors are online